2020
DOI: 10.1101/2020.06.12.148734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drift and termination of spiral waves in optogenetically modified cardiac tissue at sub-threshold illumination

Abstract: The development of new approaches to control cardiac arrhythmias requires a deep understanding of spiral wave dynamics. Optogenetics offers new possibilities for this. Preliminary experiments show that sub-threshold illumination affects electrical wave propagation in the mouse heart. However, a systematic exploration of these effects is technically challenging. Here, we use state-of-the-art computer models to study the dynamic control of spiral waves in a two-dimensional model of the adult mouse ventricle, usi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The ChR2 photocycles were simulated using an model for ChR2-H134R ( Williams et al, 2013 ), as in previous works ( Karathanos et al, 2014 , 2016 ; Bruegmann et al, 2016 ; Boyle et al, 2018b ; Hussaini et al, 2021 ). Briefly, the ChR2 was modeled as a 4-state Markov chain model with light-gated transitions between two closed (non-conducting) and two open states (permeable to cation flow).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ChR2 photocycles were simulated using an model for ChR2-H134R ( Williams et al, 2013 ), as in previous works ( Karathanos et al, 2014 , 2016 ; Bruegmann et al, 2016 ; Boyle et al, 2018b ; Hussaini et al, 2021 ). Briefly, the ChR2 was modeled as a 4-state Markov chain model with light-gated transitions between two closed (non-conducting) and two open states (permeable to cation flow).…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac optogenetics is an emerging field that stems from work involving genetic transduction of light-sensitive ion channels into mammalian neurons ( Boyden et al, 2005 ; Arrenberg et al, 2010 ). The use of light for current induction in cardiac tissue with precise spatial and temporal precision has led to in vivo studies describing selective excitation of specific cell populations ( Jia et al, 2011 ; Addis et al, 2013 ), control of spiral waves ( Burton et al, 2015 ; Hussaini et al, 2021 ), and cardiac pace-making ( Bruegmann et al, 2010 ; Ambrosi and Entcheva, 2014 ; Nussinovitch and Gepstein, 2015a ; Vogt et al, 2015 ) or arrhythmia termination in animal models ( Bruegmann et al, 2016 ; Nyns et al, 2017 , 2019 ; Cheng et al, 2020 ). In vitro applications of optogenetics have yielded all-optical methods for contactless, high-throughput measurement of electrophysiological properties like action potential duration and inter-cellular electric coupling at different spatial scales ( Klimas et al, 2016 ; Boyle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…By activating this protein in cardiomyocytes, researchers have already successfully generated optical pacemakers ( Arrenberg et al, 2010 ; Bruegmann et al, 2010 ) and conducted optical defibrillation in animal models ( Bruegmann et al, 2018 ; Bruegmann et al, 2016 ; Crocini et al, 2016 ; Nyns et al, 2017 ). Now, in eLife, Stefan Luther and colleagues – including Sayedeh Hussaini as first author – report that low-intensity light may be used to steer rotors ( Hussaini et al, 2021 ). Using a combination of cardiac optogenetics and computational modelling, they describe guiding rotors towards locations where re-entrant electrical activity is no longer possible, thereby terminating cardiac arrhythmias.…”
mentioning
confidence: 99%
“…Therefore optogenetics can be used as a valuable tool for proof-of-concept for feedback induced resonant drift. Recent numerical and experimental studies using optogenetics have demonstrated the enormous potential of this technology to be used as a tool for investigating and controlling spiral wave dynamics at supra-threshold, where an action potential occurs and is followed by excitation wave propagation [11,23,99,205,206], as well as sub-threshold [207] light intensities, where no action potential is triggered.…”
Section: Introductionmentioning
confidence: 99%